The human Lgl polarity gene, Hugl-2, induces MET and suppresses Snail tumorigenesis - Kashyap, A.; Zimmerman, T.; Erguel, N.; Bosserhoff, Anja; Hartman, U.; Alla, V.; Bataille, F.; Galle, P. R.; Strand, S.; Strand, D. (Oncogene, 2013)
Lethal giant larvae proteins have key roles in regulating polarity in a variety of cell types and function as tumour suppressors. A transcriptional programme initiated by aberrant Snail expression transforms epithelial cells to potentially aggressive cancer cells. Although progress in defining the molecular determinants of this programme has been made, we have little knowledge as to how the Snail-induced phenotype can be suppressed. In our studies we identified the human lethal giant larvae homologue 2, Hugl-2, (Llgl2/Lgl2) polarity gene as downregulated by Snail. Snail binds E-boxes in the Hugl-2 promoter and represses Hugl-2 expression, whereas removal of the E-boxes releases Hugl-2 from Snail repression. We demonstrate that inducing Hugl-2 in cells with constitutive Snail expression reverses the phenotype including changes in morphology, motility, tumour growth and dissemination in vivo, and expression of epithelial markers. Hugl-2 expression reduced the nuclear localization of Snail and thus binding of Snail to its target promoters. Our results placing Hugl-2 within the Snail network as well as its ability to suppress Snail carcinogenesis identifies Hugl-2 as a target molecule driving cascades, which may have preventative and therapeutic promise to minimize cancer progression. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: EMT; Hugl-2; Lgl; MET; Snail; tumour suppression